Expert forecasts of the impacts of tourism trends: Assessment by polish university students - Alejziak, Wiesław; Szczechowicz, Bartosz (Turyzm/Tourism, 2020)
The purpose of the article was to establish whether a tourism student can effectively recognize tourism trends, and to achieve this aim the following research tasks were accomplished: 1) the authors identified 10 trends (and 47 impacts), concerning the transformations that have occurred in tourism in recent years and have been recognized by specialists from the European Travel Commission and the European Tourism Action Group; 2) these trends and their impacts underwent a critical evaluation by students who were given the opportunity to add other impacts (their own) to the specialist list; 3) students’ evaluations were compared to current trends identified in other academic work. The research was conducted on 95 tourism and recreation students at the University of Physical Education in Kraków and the Vistula School of Hospitality in Warsaw (formerly: Warsaw School of Tourism and Hospitality Management), in 2017/2018 and 2018/2019. The article has also presented the results of earlier research (unpublished) at two other academic centres (Rzeszow and Kielce) on 113 students, 17 lecturers and 76 travel agency employees. Together the results described in this article present the opinions of 301 respondents. It was established that students, as a group, are sufficiently effective observers of changes in the tourism market to make an appropriate contribution and, consequently, are valuable participants at brainstorming sessions. They use what they have learned during their university study, are familiar with forecasting and scenario methods, as well as taking advantage of the imagination and creativity typical of such students.